Curvature Properties and η-Einstein (k, μ)-Contact Metric Manifolds. (5th November 2012) - Nagaraja, H. G.; Premalatha, C. R.
Abstract : We study curvature properties in ( k, μ ) -contact metric manifolds. We give the characterization of η -Einstein ( k, μ ) -contact metric manifolds with associated scalars.